Phytochemistry and Pharmacological Potentials of Premna serratifolia L.: Traditional Medicinal Plant Used by Local People in Kalimantan - Khairunnisa, Khalisha Qintara; Febriyanti, Raden Maya; Muhaimin, Muhaimin (Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, 2022)
Millions of people worldwide have been using herbal medicines for thousands of years, due to their great interest in traditional medicines. One of the plants in Indonesia which has medicinal properties but is not widely known by the public and used is Bebuas plant. Bebuas (Premna serratifolia Linn) has been observed growing in West Kalimantan. The people of West Kalimantan used bebuas leaves to reduce cholesterol levels, the young leaves used as a traditional medicine to expel wind in the body quickly, treat intestinal worms, and increase breast milk for nursing mothers, and the decoction of fresh leaves is used for colds and fever medicine. Several studies report bebuas (Premna serratifolia L.) had many pharmacological activities. Bebuas contains flavonoids, saponins, tannins and triterpenoids/steroids that have a role in pharmacological activity. The present review aims to summarize the current state of scientific evidence on the pharmacological potentials of P. serratifolia. The subject of literature published from 2012 to 2022 were obtained frominternational research databases including PubMed, Google Scholar, EBSCO, SCOPUS, and Cochrane, using the keywords Premna serratifolia L., traditional medicine, medicinal plants, and pharmacology. The pharmacological activities which are discussed further in the review including antioxidant, anti-arthritic, anticholesterol, anti-inflammatory, antimicrobial, antihelmintic, antidiabetic, and anticancer/cytotoxic. The study suggests that Premna serratifolia L. is a potent source for further development of phytomedicine.